2018
DOI: 10.3389/fped.2018.00292
|View full text |Cite
|
Sign up to set email alerts
|

Aggressive NK-Cell Leukemia

Abstract: Aggressive NK cell leukemia (ANKL) is a rare malignant lymphoproliferative disorder of mature NK cells closely associated with Epstein-Barr virus (EBV) and more common in East Asia than in other areas. Significant variations exist in the morphology of ANKL tumor cells, from typical large granular lymphocyte morphology to highly atypical features with basophilic cytoplasm containing azurophilc granules. The main involved sites are hepatosplenic lesions, bone marrow and peripheral blood, and nasal or skin lesion… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
47
1
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(50 citation statements)
references
References 41 publications
1
47
1
1
Order By: Relevance
“…Nonetheless, due to a limited sample size and follow-up time, this finding requires confirmation by more studies. In addition, the level of LDH in peripheral blood is often considered to be correlated with the prognosis of patients with lymphoproliferative diseases [8]. Among the patients included in our study, 5 of 7 patients with elevated LDH eventually died, which further confirmed this conclusion.…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…Nonetheless, due to a limited sample size and follow-up time, this finding requires confirmation by more studies. In addition, the level of LDH in peripheral blood is often considered to be correlated with the prognosis of patients with lymphoproliferative diseases [8]. Among the patients included in our study, 5 of 7 patients with elevated LDH eventually died, which further confirmed this conclusion.…”
Section: Discussionsupporting
confidence: 86%
“…In recent years, many scholars have made important contributions to research in EBV-related lymphoproliferative diseases, leading to breakthroughs in genomic exploration. Nonetheless, relevant studies have mostly focused on EBV T/natural killer (NK) cell lymphoproliferative diseases or chronic active EBV (CAEBV) infection [7][8][9][10], and sequencing for HVLPD has rarely been performed. HVLPD shares many common features with EBV T/NK cell lymphoproliferative diseases or CAEBV without HVLPD, including high levels of EBV DNA in the blood (primarily inTor NK cells) and a high frequency of clonal T cells.…”
Section: Introductionmentioning
confidence: 99%
“…ANKL is characterised by CD2 + , CD16 + and CD56 + cells positive for cytotoxic molecules. High serum levels of CXCR1 indicated increased CD56 DIM NK cell activity resulting in necrosis, apoptosis and organ failure [ 49 ]. In stark contrast to the expansion of NK cells in ANKL, syndromes characterised by severely diminished NK cell numbers and NK cell subsets also exist.…”
Section: Unbalanced Immune Responses In Autoimmune and Systemic Comentioning
confidence: 99%
“…Despite intensive chemotherapy, patients with ANKL have a very poor prognosis, with a median survival of less than two months [ 20 , 21 ]. Several prognostic factors have been proposed, including patient age, serum lactate dehydrogenase level, and serum total bilirubin level [ 22 ], but these factors have not been validated [ 23 ]. The clinicopathologic features of ANKL have been elucidated in several case series [ 19 , 20 , 21 , 24 , 25 , 26 , 27 ].…”
Section: Clinical Featuresmentioning
confidence: 99%
“…No consensus chemotherapeutic regimen has been established to manage patients with ANKL as the rarity of this disease has precluded prospective clinical trials [ 23 ]. Current knowledge of therapy is based on small clinical studies focused on chemotherapeutic approaches and clinical outcomes.…”
Section: Treatment Of Anklmentioning
confidence: 99%